Advances in Network Security and Applications 4th International Conference, CNSA 2011, Chennai, India, July 15-17, 2011 - Wyld, David C.; Wozniak, Michal; Chaki, Nabendu; Meghanathan, Natarajan; Nagamalai, Dhinaharan; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the 4th International Conference on Network Security and Applications held in Chennai, India, in July 2011. The 63 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers address all technical and practical aspects of security and its applications for wired and wireless networks and are organized in topical sections on network security and applications, ad hoc, sensor and ubiquitous computing, as well as peer-to-peer networks and trust management.
Electronic reproduction.
Keywords: Computer science; Computer Communication Networks; Software engineering; Data encryption (Computer science).; Computer software; Information systems; Information Systems; Electronic books